Salmona´s idea of city report on an analysis of the human science postgraduate building (2009)
This article is a comparative study between the Park Towers and the building of Postgraduate Studies of Human Sciences Faculty, at the National University of Colombia designed by the architect Rogelio Salmona. Reviewing both constructions the interaction between building and city, and by the use of social aspects as ‘the encounter with the other’ and the politics, we hope to find that original idea, referred to the city, which sustains conceptually the work of this architect, which we believe concerns to the Greek notion of polis.